Zeszyt kontaktów jako narzędzie komunikacji szkolnej - Szczerbińska, Barbara (Dydaktyka Polonistyczna, 2017)
The most important features in education process are effective communication, exchange of informations between school and parents about student’s progress, organizational and tutelary- educational matters. The subject of article considers speculations about structure, style and pragmatic aspect of inscriptions put in issue notebook as the matter of communication between teacher and the student’s family home. Four notebooks, which were shared by the parents for the purposes of this research paper, were elaborately analysed. To the fore of interaction between the teacher and student’s home environment come such forms of linguistic behaviours which may be considered as complaints, questions or requests. Some of them sound like charges, regrets over one’s behaviour and proceeding. Parents also occur in the role of the sender- they write justifications or excusals from classes if needed. The most common forms of language are in official and elevated style.